2019
DOI: 10.1093/conphys/coz074
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive methods to measure inter-renal function in aquatic salamanders—correlating fecal corticosterone to the environmental and physiologic conditions of captive Necturus

Abstract: We measured faecal corticosterone metabolites (fCMs) in aquatic salamander Necturus to understand how inter-renal function changes throughout seasonal environmental changes and associated reproductive activity. fCMs elevated with lower water temperatures and breeding activity. To overcome some challenges associated with faecal hormone collection/analysis, waterborne corticosterone (wCM) was validated through ACTH challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, the American toad had no response to the saline injection ( Santymire et al , 2018 ). Similarly, in ACTH challenges with waterborne corticosterone in aquatic salamanders, Gabor et al (2016 ) and Nagel et al (2019) found no significant difference in waterborne corticosterone in ACTH and saline treatments, but Gabor et al (2016) found that ACTH-treatment salamanders exhibited higher GCs than non-injected control salamanders.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the American toad had no response to the saline injection ( Santymire et al , 2018 ). Similarly, in ACTH challenges with waterborne corticosterone in aquatic salamanders, Gabor et al (2016 ) and Nagel et al (2019) found no significant difference in waterborne corticosterone in ACTH and saline treatments, but Gabor et al (2016) found that ACTH-treatment salamanders exhibited higher GCs than non-injected control salamanders.…”
Section: Discussionmentioning
confidence: 93%
“…Dermal swabs can be quickly collected within 30 seconds, adding minimal handling time to the established sampling protocol. Recent work has used water sampling, where an amphibian is placed in a set amount of water for ~15 minutes up to several hours, thus allowing GCs to be secreted in the water ( Reedy et al , 2014 ; Gabor et al , 2016 ; Forsburg et al , 2019 ; Nagel et al , 2019 ). However, it is difficult to determine if the GCs measured are in response to the animal’s environment or to being put in the container.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the aquatic environment also makes it difficult to collect urine and feces (see Figure 1 in [ 28 ]). In amphibians, researchers have analyzed hormones using a water container and quantified the concentration of GCs in a known amount of water [ 29 , 30 , 31 , 32 ]. Additionally, GCs have been collected using dermal swabs and have been validated for several amphibian species [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%